Analisis Pengelolaan Modal Kerja Terhadap Tingkat Laba Pada PT. Perkebunan Nusantara III Tanah Raja - Alma Pradita (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2021)
This study aims to determine the Analysis of Working Capital Management Against Profit Levels at PT. Nusantara III Plantation, Tanah Raja. This study uses a qualitative descriptive approach, aims to determine the Management of Working Capital Against Profit Levels at PT. Nusantara III Plantation, Tanah Raja. The subject of this research is PT. Perkebunan Nusantara III Tanah Raja and the object of this research is the report on working capital and profit at PT. Nusantara III Tanah Raja Plantation for 3 years, 2018-2020. Based on the results of the study, it can be concluded that working capital on the company's operating profit level at PT. Perkebunan Nusantara III Tanah Raja, namely the effective use of working capital can affect the company's profit level. This is seen from the level of profit which has increased due to an increase in working capital turnover. This can also be seen in 2020, the profit rate of PT. Perkebunan Nusantara III Tanah Raja has increased due to the turnover of capital at PT. The Nusantara III Tanah Raja Plantation in 2020 also experienced an increase. Likewise, the profit level of PT. Perkebunan Nusantara III Tanah Raja in 2019 experienced a decline followed by a decrease in profit turnover so it can be concluded that working capital turnover can affect the company's profit level.